Host Genotypic Effect on Algal Symbiosis Establishment in the Coral Model, the Anemone Exaiptasia diaphana, From the Great Barrier Reef - Tortorelli, Giada; Belderok, Roy; Davy, Simon K.; McFadden, Geoffrey I.; van Oppen, Madeleine J. H. (Frontiers in Marine Science, 2020)
The mutualistic symbiosis between cnidarians and photosynthetic dinoflagellates supports one of the most diverse ecosystems on the planet, coral reefs. Cnidarian-Symbiodiniaceae symbioses are broadly species-specific, but little is known about the mechanisms underpinning this specificity. Here, we explored the ability of three genotypes of the sea anemone Exaiptasia diaphana (Aiptasia)—a model organism for the cnidarian-dinoflagellate symbiosis—from the Great Barrier Reef (GBR), to take up and maintain seven different Symbiodiniaceae strains. A method to track the number of symbiont cells by quantitative microscopy of algal chlorophyll auto-fluorescence in the anemone tentacles was developed. Breviolum minutum, the homologous (i.e. native) symbiont in these anemones, was the most successful of the seven algal types tested at colonizing aposymbiotic anemones of all three genotypes. The heterologous (i.e. non-native) but compatible species Cladocopium goreaui was also able to colonize GBR anemones, albeit at lower cell densities. Durusdinium trenchii, Fugacium kawagutii, ‘Symbiodinium F5.1’ and ‘Symbiodinium G3’ showed little or no ability to colonize any E. diaphana genotype, and Symbiodinium tridacnidorum, isolated from clams, apparently killed the anemones. Histology localized the homologous and compatible heterologous symbionts within the endodermis of the host, but appreciable numbers of C. goreaui cells were not fully internalized by anemone cells. Colonization dynamics were influenced by symbiont type and host genotype, suggesting that a mechanism of recognition and incorporation has components in both symbiont and host. The matrix of different host-symbiont compatibilities described here can be used to explore the molecular mechanisms of recognition and establishment of cnidarian-Symbiodiniaceae symbiosis.